Parenting Experiences in Shaping Sleep Routines for Children with Attention-Deficit/Hyperactivity Disorder (ADHD): A Phenomenological Study - Rahmaningrum, Ainulia Salsabila; Tri Budi Santoso; Tri Winarno (Jurnal Keterapian Fisik, 2024)
Background: Parenting styles influence sleep routines and problems in children with Attention-Deficit/Hyperactivity Disorder (ADHD); sleep quality includes efficiency, latency, duration, and wakefulness after onset. This study explores the experience of implementing bedtime routines based on caregiver parenting styles and their implications for the sleep quality of children with ADHD. Methods: Qualitative study with a phenomenological approach; non-probability sampling (purposive sampling). Participants consisted of 8 caregivers (mothers, aunts, grandmothers) of children with ADHD at YPAC Surakarta; semi-structured in-depth interviews were conducted 2–3 times per participant and analyzed thematically with credibility and confirmability tests. Results: Three main themes emerged: (1) Caregiver parenting styles (implementation and influence on sleep), (2) Types of parenting styles based on Baumrind's aspects, (3) Sleep quality of children with ADHD (sleep quality, sleep problems, supporting factors). Authoritarian parenting was linked to a stable sleep schedule but had no impact on efficiency; democratic parenting influenced emotional regulation; permissive parenting had no apparent effect on sleep quality; neglectful parenting was associated with sleep-onset insomnia without a clear cause. Conclusion: Variations in parenting styles result in different profiles of impact on sleep quality indicators. Education and harmonization of parenting styles are recommended in pediatric occupational therapy services.